2023
DOI: 10.3389/fphar.2023.1146741
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds ursolic acid and digoxin exhibit inhibitory activities to cancer cells in RORγ-dependent and -independent manner

Abstract: Natural compounds ursolic acid (UA) and digoxin isolated from fruits and other plants display potent anti-cancer effects in preclinical studies. UA and digoxin have been at clinical trials for treatment of different cancers including prostate cancer, pancreatic cancer and breast cancer. However, they displayed limited benefit to patients. Currently, a poor understanding of their direct targets and mechanisms of action (MOA) severely hinders their further development. We previously identified nuclear receptor R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Concomitantly, UA disrupted RORγ-controlled apoptosis/cell cycle genes. In conclusion, UA elicits its antiproliferative effect against PCa and TNBC, in part, via targeting RORγ [117].…”
Section: Modulation Of Retinoic Acid Receptor-related Orphan Receptor...mentioning
confidence: 89%
See 1 more Smart Citation
“…Concomitantly, UA disrupted RORγ-controlled apoptosis/cell cycle genes. In conclusion, UA elicits its antiproliferative effect against PCa and TNBC, in part, via targeting RORγ [117].…”
Section: Modulation Of Retinoic Acid Receptor-related Orphan Receptor...mentioning
confidence: 89%
“…A recent interesting report by Zou et al emphasized the RORγ-dependent anti-proliferative role of UA against triple negative breast cancer (TNBC) cells, HCC70, and prostate cancer (PCa) cell lines C4-2B and 22Rv1 [117]. In the test cell lines, UA lowered RORγ activation, as shown by a luciferase reporter assay, in a dose-dependent manner.…”
Section: Modulation Of Retinoic Acid Receptor-related Orphan Receptor...mentioning
confidence: 98%
“…Studies have suggested that Digoxin possesses anti-proliferative properties against prostate cancer and breast cancer cells. [ 50 ] Digoxin demonstrates potential therapeutic benefits for non-small cell lung cancer in humans by inhibiting the phosphorylation of a protein kinase implicated in tumor cell survival, proliferation, metastasis, and autophagy within the PI3K/Akt pathway signaling. Nevertheless, further proof is required to support these conclusions.…”
Section: Discussionmentioning
confidence: 99%